The LEM-ESCRT toolkit: Repair and maintenance of the nucleus - Borah, Sapan; Dhanasekaran, Karthigeyan; Kumar, Santosh (Frontiers in Cell and Developmental Biology, 2022)
The eukaryotic genome is enclosed in a nuclear envelope that protects it from potentially damaging cellular activities and physically segregates transcription and translation. Transport across the NE is highly regulated and occurs primarily via the macromolecular nuclear pore complexes. Loss of nuclear compartmentalization due to defects in NPC function and NE integrity are tied to neurological and aging disorders like Alzheimer’s, viral pathogenesis, immune disorders, and cancer progression. Recent work implicates inner-nuclear membrane proteins of the conserved LEM domain family and the ESCRT machinery in NE reformation during cell division, NE repair upon rupture in migrating cancer cells, and in generating seals over defective NPCs. In this review, we discuss the recent in-roads made into defining the molecular mechanisms and biochemical networks engaged by LEM and many other integral inner nuclear membrane proteins to preserve the nuclear barrier.